Microbial signature of intestine in children with allergic rhinitis - Zhang, Panpan; Zhou, Xuehua; Tan, Hong; Jian, Fangfang; Jing, Zenghui; Wu, Huajie; Zhang, Yao; Luo, Jianfeng; Zhang, Juan; Sun, Xin (Frontiers in Microbiology, 2023)
Introduction: Previous studies have found that unique patterns of gut microbial colonization in infancy associated with the development of allergic diseases. However, there is no research on the gut microbiota characteristics of AR children in Chinese Mainland. Objective: To investigate the changes of gut microbial of AR children in Chinese Mainland and evaluate the correlation between gut microbial and clinical indexes. Methods: In this clinical study, fecal samples from 24 AR children and 25 healthy control children (HCs) were comparative via next generation sequencing of the V3-V4 regions of the 16S rRNA gene.Analyzed the relationship between clinical features and gut microbial using Spearman correlation.Results: Compared to HCs, AR children showed significant decreases in Shannon index and significant increases in Simpson index at both the family and genera levels (all p< 0.05). In terms of bacterial composition, at the phylum level, AR children had higher abundance of Bacteroidetes than that in the HCs group (p< 0.05) and were significantly positively correlated with TNSS (p< 0.05). At the family level, AR children had higher abundance of Prevotellaceae and Enterobacteriaceae higher than that in the HCs group (all p< 0.05) and had a significantly positive correlation with TNSS, eosinophils (EOS) and total immunoglobulin E (tIgE) (all p< 0.05). At the genus level, reduced abundance of Agathobacter, Parasutterella, Roseburia and Subdoligranulum were also observed in the AR cohorts compared to HCs (all p< 0.05) and significantly negatively associated with TNSS, EOS, tIgE, QOL and FeNO (all p< 0.05).Chinese Mainland were characterized by reduced microbial diversity and distinguished microbial characteristics in comparison with HCs. The observations of this study offer proof that distinctive gut microbiota profiles were present in AR children and necessitate further investigation in the form of mechanistic studies 1